Recontextualization of Ibn Sina's Thoughts in the Development of Islamic Religious Education Pedagogy Based on Science and Ethics - Muhammad Haikal Saputra; Muhammad Abdul Aziz Al-Maghribi; Ilham Romadona; Supardi Ritonga (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This article aims to recontextualize Ibn Sina’s thoughts on intellectual development, stages of learning, and the relationship between knowledge and ethics in the development of Islamic Religious Education (IRE) pedagogy in the digital era. Employing a qualitative-descriptive approach through library research, this study examines Ibn Sina’s primary works alongside contemporary literature on Islamic pedagogy and education. The discussion addresses current challenges in IRE pedagogy, including students’ ethical crises, weak reasoning habits, and the persistent dichotomy between religious knowledge and scientific disciplines. The findings indicate that IRE pedagogy can be strengthened through an investigative and value-based learning model, in which students are guided to verify information (tabayyun), engage in reflective thinking (tafakkur) on scientific and social phenomena, consider ethical implications, and translate these reflections into concrete actions. This article highlights Ibn Sina’s theoretical contribution as an epistemological bridge between scientific rationality and Islamic spirituality in developing a holistic, relevant, and transformative IRE pedagogy.